Implementing a Fetal Health Surveillance Guideline in Clinical Practice: A Pragmatic Randomized Controlled Trial of Action Learning. Issue 5 (October 2015) - Snelgrove‐Clarke, Erna; Davies, Barbara; Flowerdew, Gordon; Young, David
ABSTRACT Aims The aim of this study was to determine the effects of an Action Learning intervention on nurses' use of a fetal health surveillance (FHS) guideline during labor of women who were low risk on admission for delivery. Methods Using a pragmatic randomized controlled trial, nurses were randomized to Action Learning (n = 44) or Usual Care (n = 45). Low‐risk women were assigned to either an Action Learning nurse (n = 122) or a Usual Care nurse (n = 148). Data on practices during an episode of care (nurses' FHS practices from admission through to delivery in low‐risk women) were collected at three trial time points: 1 month prior, during 6 months, and 1 month following. Guideline adherence, women's perception of birth experience, and enablers and inhibitors to intermittent auscultation (IA) were collected. Multivariate logistic regression determined the variables (chosen by the nurses) that predicted Action Learning nurses' adherence to FHS practices. Findings Statistically significant change was not evident between nurses' rate of FHS practices in the Action Learning group compared with Usual Care (Δ6.8%, odds ratio [OR] 0.16, 95% confidence interval [CI] 0.84–2.83). Postpartum, women reported high satisfaction with no significant difference by study group. Two labor events, epidural and narcotic analgesia, most influenced guideline appropriate care (p = .000, OR –4.04; p = .000, OR = 2.89) within the experimental group. Linking Evidence to Action Despite lack of between‐group significant changes in FHS practices, Action Learning nurses, who chose areas of practice that presented obstacles to their guideline adherence ability (epidurals and narcotics), significantly changed their FHS practices. Researchers need to consider whether practice is long‐standing acceptance of the evidence by healthcare providers, and the provider's intentions for implementation effectiveness when choosing an implementation strategy. Supportive nurses, Doppler availability, and clear policies support adherence to an IA guideline. Deimplementation of ineffective practice is warranted.